Strategi Prekrutan Calon Mahasiswa Program Studi Matematika dengan Metode Roadshow di MA Abdussatar Kediri, Lombok Barat - Irma Risvana Dewi; Dara Puspita Anggraeni; Dwi Agustini; Alfian Eka Utama; Rio Satriyantara (Pendidikan Matematika, FKIP Universitas Mataram, 2022)
The promotion aims to attract prospective students to enter University. Socialization can introduce higher education institutions to senior high school students. One of the most effective ways to attract prospective students is the school visit or roadshow program. This program was carried out by lecturers and students of the mathematics division, UNW FMIPA, on May 2022 at MA Abdussatar Kediri, West Lombok. The roadshow program was attacked and got a positive response from MA Abdussatar teachers and students. The activity has given students motivation, insight, and knowledge regarding the existence of a mathematics study program at Nahdlatul Wathan University Mataram. Hopefully, this program can increase the motivation of the students to continue their education to a higher level.